A Lighting Control System in Buildings based on Fuzzy Logic - Seno D. Panjaitan; Aryanto Hartoyo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Lighting generally consumed 25%-50% of total electricity consumption in a building. Nowadays, the building lighting source is dominated by the use of fluorescent lamps. The previous technical papers by other researchers had focused on power density control of incandescent lamps, which is now rarely used, unconsidered national standard as control reference value, and required a high-cost in investment. By these reasons, this paper proposes a building lighting system based on fuzzy logic scheme to automate fluorescent lamps in order to achieve illumination according to Indonesian National Standard (SNI). The input variables were indoor lighting, inference from outdoor lighting, and occupancy. The output variable was the required illumination to achieve the standard. The required illumination determined the number of lamps that had to be turned on. In the experiment result, a classroom illumination of lighting without controller in workdays was about 350 lux, while with the proposed controller it varied between 250–300 lux close to the SNI, i.e. 250 lux. Meanwhile, with the proposed controller the electricity consumption for a classroom was 75% lower than the lighting without controller.